ON CORRECTNESS OF BAYES FORMULA - Alexander Ivanovich Dolgov (Advanced Engineering Research)
The inadmissibility of the comparison and cooperative processing of the conditional probabilities calculated with the use of the known variations of Bayes formula considering a well-defined amount of the accumulated evidences is established. This statement is justified as follows. Due to the unequal normalization, the results leading to the conclusions mismatching the probability-theoretical law are obtained. The examples of the concrete initial data show that in the case of using the traditional formulas, the multiplicative effect is missing: reducing the posteriori conditional probabilities of each of the hypotheses under the multiplicative accumulating evidences is unfeasible. The Bayesian formula modifications are offered. They provide a well-defined quantity of sequentially accumulated evidences constructed through the common divisor which is equal to the sum of the values of all normalizable probabilities liable to comparison or cooperative processing. In contrast to the well-known formulas, due to the correct normalization, the results significantly more adequate to the initial statistics are obtained.